Does the Rabbit's Foot Actually Work? The Causal Effect of Foreign Ownership on Firm Productivity in Three ASEAN Countries - Inggrid Inggrid (Institute of Research and Community Outreach - Petra Christian University, 2015)
Voluminous studies have examined the relationship between foreign ownership and firm productivity. Two general patterns emerge at the empirical level: they are essentially correlational and results are mixed. This paper estimates the causal effect of foreign presence on a variety of productivity measures. We rely on a selection on observables approach based on the idea that all variables that influence foreign ownership status and firm productivity are fully captured by the available control variables, eliminating the problem of selection bias. Using firm-level data from three ASEAN countries, the study finds that productivity of foreign-owned firms is consistently above that of domestically-owned firms regardless of different productivity measures and types of matching algorithms. This result suggests to a large extent the benefits of foreign participation in the economy.